Professionalism of physical education teachers: from the leadership of school principals, school culture to teacher work motivation - Sinulingga, Albadi; Suprayitno, Suprayitno; Pertiwi, Dian (Universitas Nusantara PGRI Kediri, 2019)
This study aims to obtain an overview of the relationship between school principal leadership, school culture and teacher work motivation on the professionalism of physical education teachers. The study uses a quantitative approach with the Ext-Post Facto method. The population in this study amounted to 952 people from 34 Public and Private Vocational High Schools (SMK) registered in MGMP (Subject Teachers' Consultation) Physical Education Vocational School Physical Education Serdang Bedagai Regency in North Sumatra Province in 2017. Samples of 30 physical education teachers from 34 Schools using purposive sampling techniques. Data collection techniques using a questionnaire. Data analysis techniques using path analysis. The results showed that the principal's leadership and work motivation of teachers directly affected teacher professionalism, while school culture would not affect teacher professionalism. The conclusion is that the principal's good leadership, healthy school culture, and high teacher motivation are factors of high and low teacher professionalism.